Analysis of Murabahah Financing Marketing Strategy in Attracting Indonesian Sharia Bank (BSI) Customers at KC Stabat - Ayu Syahvitri; Sugianto Sugianto (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Murabahah financing is one of the consumptive financing for purchasing necessities such as buying vehicles, building houses, and renovating houses. The payment is from a permanent salary source or employees such as civil servants, which every month will be deducted directly from the salary. And the contract used is in accordance with customer needs. This research is studied to find out whether this murabahah financing product can attract a large number of customers, considering that Indonesia is a country where the majority are Muslims. By using a marketing mix strategy, in the marketing mix theory proposed by Ali Hasan, there are 4 marketing strategies that must be applied by banks in order to attract prospective customers to take murabahah financing products. The 4P marketing mix strategy includes product, price, promotion, place, people, process, and physical evidence. By analyzing using SWOT analysis, it can be concluded that the marketing mix strategy used is very influential on the addition of multipurpose financing customers at Bank Syariah Indonesia KC Stabat.